Human papillomavirus associated cervical lesion: pathogenesis and therapeutic interventions - Jiatian Ye; Lan Zheng; Yuedong He; Xiaorong Qi (MedComm, 2023)
Abstract Human papillomavirus (HPV) is the most prevalent sexually transmitted virus globally. Persistent high‐risk HPV infection can result in cervical precancerous lesions and cervical cancer, with 70% of cervical cancer cases associated with high‐risk types HPV16 and 18. HPV infection imposes a significant financial and psychological burden. Therefore, studying methods to eradicate HPV infection and halt the progression of precancerous lesions remains crucial. This review comprehensively explores the mechanisms underlying HPV‐related cervical lesions, including the viral life cycle, immune factors, epithelial cell malignant transformation, and host and environmental contributing factors. Additionally, we provide a comprehensive overview of treatment methods for HPV‐related cervical precancerous lesions and cervical cancer. Our focus is on immunotherapy, encompassing HPV therapeutic vaccines, immune checkpoint inhibitors, and advanced adoptive T cell therapy. Furthermore, we summarize the commonly employed drugs and other nonsurgical treatments currently utilized in clinical practice for managing HPV infection and associated cervical lesions. Gene editing technology is currently undergoing clinical research and, although not yet employed officially in clinical treatment of cervical lesions, numerous preclinical studies have substantiated its efficacy. Therefore, it holds promise as a precise treatment strategy for HPV‐related cervical lesions.